N400 Amplitude Reduction Correlates with an Increase in Pupil Size - Kuipers, Jan Rouke; Thierry, Guillaume (Frontiers in Human Neuroscience, 2011)
Pupil dilation is classically associated with increase in cognitive load in humans. Here, we studied the potential link between human pupil dilation and meaning integration effort as indexed by event-related brain potentials (ERPs). We recorded pupil size variation and ERPs simultaneously while participants were presented with matching or unrelated picture-word pairs. Whilst relatedness in meaning between spoken words and pictures typically modulated ERPs, pupil size was also affected quickly after picture onset. Moreover, during the time-window associated with meaning integration, greater pupil dilation correlated with less negative N400 amplitudes elicited by unrelated pictures. Since pupil dilation has been linked to activity of the Locus Coeruleus-Norepinephrine (LC-NE) system, these findings provide new insights into the suggested link between human high-level cognitive function and activity of the LC-NE system.